Uma aplicação do método dos elementos de contorno a problemas de contacto - Motter, José Geraldo (1991)
This work is concerned with the development of a computer program for evaluation of 2-D plane strain or plane stress contact problems between two elastic bodies with frictional forces on the contact surfaces, by means of the boundary element method. The half-plane fundamental solution is implemented in order to efficiently improve the solution of contact problems involving semi-infinite media.